1985
DOI: 10.1139/v85-578
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of o-quinodimethane with p-quinones: synthesis of tetrahydro-1,4-anthracenediones

Abstract: . Can. J. Chem. 63, 3526 (1985). Previous work from our laboratory has been concerned with investigating the photochemical reactivity of the tetrahydro-1,4-napthalenedione system, both in solution and the solid state. The results obtained prompted us to extend our studies to the analogous tetrahydro-l,4-anthracenedione system. The most direct method of synthesis of the desired compounds is through Diels-Alder addition of o-quinodimethane to p-quinones. Because of the ease with which the adducts would be expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The route which has attracted more attention during the last years has been the oQDM generation via sultines, which were first synthesized by Durst and co-workers . Generation of oQDM from sultine ( 45 , 4,5-benzo-3,6-dihydro-1,2-oxathiin-2-oxide) has advantages over methods involving metals and dihalide, which cannot be used in the presence of reducible groups, or the fluoride ion catalyzed decomposition of { o -[(trimethylsilyl)methyl]benzyl}trimethylammonium bromide, because enolization can take place in the quinone adducts . On the other hand, while sulfone 46 is stable and requires temperatures around 300 °C to generate oQDM, sultines are known to require lower thermolysis temperature for the cheletropic elimination of SO 2 .…”
Section: From Benzo-fused Heterocyclic Compoundsmentioning
confidence: 99%
“…The route which has attracted more attention during the last years has been the oQDM generation via sultines, which were first synthesized by Durst and co-workers . Generation of oQDM from sultine ( 45 , 4,5-benzo-3,6-dihydro-1,2-oxathiin-2-oxide) has advantages over methods involving metals and dihalide, which cannot be used in the presence of reducible groups, or the fluoride ion catalyzed decomposition of { o -[(trimethylsilyl)methyl]benzyl}trimethylammonium bromide, because enolization can take place in the quinone adducts . On the other hand, while sulfone 46 is stable and requires temperatures around 300 °C to generate oQDM, sultines are known to require lower thermolysis temperature for the cheletropic elimination of SO 2 .…”
Section: From Benzo-fused Heterocyclic Compoundsmentioning
confidence: 99%
“…Reports of end functionalized linear acene syntheses are rare, apparently due to their difficulty in synthesis. , Here we devised a new and general synthesis (shown in Scheme ) that provides the substituted tetracene derivatives. The key step utilizes a Diels−Alder cyclization to couple two easily prepared pieces: the exocyclic diene , (derived from the in situ loss of sulfur dioxide from the cyclic sulfinate ester 2 ) and the 6,7-dimethoxy naphthoquinone 3 . , Instrumental for a clean synthesis is the intermediate reduction of the quinone to the tetrone. Reduction to the acene followed by unmasking of the hydroxyl groups with boron tribromide provides the target structure.…”
mentioning
confidence: 99%
“…The key step utilizes a Diels-Alder cyclization to couple two easily prepared pieces: the exocyclic diene 22,23 (derived from the in situ loss of sulfur dioxide from the cyclic sulfinate ester 2) and the 6,7-dimethoxy naphthoquinone 3. 24,25 Instrumental for a clean synthesis is the intermediate reduction of the quinone to the tetrone. Reduction to the acene followed by unmasking of the hydroxyl groups with boron tribromide provides the target structure.…”
mentioning
confidence: 99%
“…We first examined the reaction of simple o -quinodimethane, generated in situ from 2-[(trimethylsilyl)methyl]benzyl phenyl carbonate ( 1a ) and a fluoride ion, with hexabutylditin ( 2 ) in the presence of bis( dibenzylideneacetone)palladium-diphenyl-2-pyridylphosphine (Ph 2 P(2-Py)) and observed that the exo -diene moiety was inserted into the Sn−Sn σ-bond to produce the distannylation product, α,α‘-bis(tributylstannyl)- o -xylene ( 3a ) in 55% yield (Scheme ). The reactions using other o -quinodimethane precursors or ligands also gave 3a , although the yields were rather low…”
mentioning
confidence: 99%